2017
DOI: 10.1111/apa.13700
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating tablets and capsules given to hospitalised children in Norway is common practice

Abstract: Manipulation of oral medication was regularly performed on paediatric wards. There is an urgent need for age-appropriate medicines, documented and standardised processes for manipulating medicines and staff training on the consequences of manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 23 publications
5
38
1
12
Order By: Relevance
“…Within our study, this was observed for both ciprofloxacin tablets and itraconazole liquid. Both the reasons and methods used for manipulation by parents and caregivers and nurses were similar to the Norwegian and UK studies, with taste being the most cited barrier to administration in the outpatient setting .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Within our study, this was observed for both ciprofloxacin tablets and itraconazole liquid. Both the reasons and methods used for manipulation by parents and caregivers and nurses were similar to the Norwegian and UK studies, with taste being the most cited barrier to administration in the outpatient setting .…”
Section: Discussionmentioning
confidence: 57%
“…An electronic questionnaire was built using the web‐based LimeSurvey version 2.06 (LimeSurvey GmbH, Hamburg, Germany). The questions were derived from sources regarding the manipulation of medicines for paediatric administration, such as the MODRIC guidelines, and additional research regarding manipulation of medication in children . Questions gave insight into the extent, reasons and methods of manipulation of oral dosage forms for children by parents and caregivers, and included six topics: demographic data, current medication, methods and reasons for manipulation, medication adherence in relation to manipulation, the possible combined administration of oral medicines and the sources of information consulted regarding manipulation.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of age-appropriate medicines is also generating the need to physically modify drug products. This manipulation concerns mainly solid oral dosage forms and is done to enable the administration of an appropriate dose or enhance medicine administration [3,4]. The typical methods for manipulating solid dosage forms are the splitting and crushing of tablets, opening of capsules and dispersing powder in liquid or food [4].…”
Section: Introductionmentioning
confidence: 99%
“…A manipulação de medicamentos na pediatria para ajuste de dose individual, incluindo a partição de comprimidos, é algo comum e comprimidos divididos são frequentemente usados na prática clínica para atingir a dose prescrita [6][7][8] . A falta de disponibilidade de variadas formas farmacêuticas de quimioterápicos, utilizados para o tratamento de leucemias agudas de crianças e adolescentes, faz com que esses medicamentos sejam manipulados para atender às demandas pediátricas 9,10 .…”
Section: Introductionunclassified
“…Isso pode ser problemático, considerando que grande parte dos antineoplásicos são citotóxicos e agentes perigosos, podendo causar danos às pessoas que estão envolvidas na preparação, na administração de medicamentos e no cuidado de quem está em quimioterapia 11-14 , já que a partição de comprimidos em um ambiente não controlado as expõe à poeira citotóxica 10 . Além disso, a manipulação também é preocupante por conta de questões que incluem estabilidade, biodisponibilidade e precisão da dosagem do medicamento, podendo ser administradas doses tóxicas ou subterapêuticas para a criança/adolescente 6,8 . Isso se torna mais relevante levando em consideração que os quimioterápicos têm um índice terapêutico estreito, então a administração correta é crucial para que se tenha eficácia e segurança 15 .…”
Section: Introductionunclassified